Peranan Camat dalam Membina Penyelenggaraan Pemerintahan Kelurahan di Kecamatan Ratahan Kabupaten Minahasa Tenggara - Ratuliu, Leizy Lianty; LALOMA, ALDEN; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Organization of the Government is required in order to have a good quality of work so it can be and start working professionally as well as strengthening the power of lowering public sector organizations. The ability to be competitive can only be shown through the mastery of technical work including mastery of modern technology which is currently the main requirement for being tlah each organization in order to increase productivity and competence the Organization publicly. The purpose of this research is to know the role of the head of the Organization of the Government in the construction of subdistricts in Southeast Minahasa Regency Ratahan. this method used in this research is the way is the qualitative research methods. Qualitative research is used in order to examine the conditions of natural kujungi which is its current status is a key instrument of liquid. The results showed that the role of the head of the Organization of the Government in building the village s good, them is head of s do become basic tasks and functions as leader in Ratahan. In this case the construction of the quality of work the employee s felt by his servants, ranging from the enforcement of discipline with tighter again, his goal in order to get good quality employees and professionals in and start working. The construction of the ability technically, is head of giving encouragement and continue to encourage every employee to update any ability they possess skills to more developed again. Coaching in the use of technology by providing training in operating computers and technology tools to another. However it still contained some shortcomings and constraints so that the impact on the Organization of village government that has not been the maximum.Key Words: The Role Of The Head Of The Organization Of The Government,